Cigarette smoke induced autophagy-impairment regulates AMD pathogenesis mechanisms in ARPE-19 cells. - Viren Kumar Govindaraju; Manish Bodas; Neeraj Vij (PLoS ONE, 2017)
Age related macular degeneration (AMD) is one of the leading causes of blindness. Genetics, environmental insult, and age-related factors all play a key role in altering proteostasis, the homeostatic process regulating protein synthesis, degradation and processing. These factors also play a role in the pathogenesis of AMD and it has been well established that cigarette smoking (CS) initiates AMD pathogenic mechanisms. The primary goal of this study is to elucidate whether CS can induce proteostasis/autophagy-impairment in retinal pigment epithelial (RPE) cells. In our preliminary analysis, it was found that cigarette smoke extract (CSE) induces accumulation of ubiquitinated proteins in the insoluble protein fraction (p < 0.01), which was subsequently mitigated through cysteamine (p < 0.01) or fisetin (p < 0.05) treatment. Further, it was verified that these CSE induced ubiquitinated proteins accumulated in the peri-nuclear spaces (p<0.05) that were cleared- off with cysteamine (p < 0.05) or fisetin (p < 0.05). Moreover, CSE-induced aggresome-formation (LC3B-GFP and Ub-RFP co-localization) and autophagy-flux impairment was significantly (p<0.01) mitigated by cysteamine (p<0.05) or fisetin (p<0.05) treatment, indicating the restoration of CSE-mediated autophagy-impairment. CSE treatment was also found to induce intracellular reactive oxygen species (ROS, p < 0.001) while impacting cell viability (p < 0.001), which was quantified using CMH2DCFDA-dye (ROS) and MTS (proliferation) or propodium iodide staining (cell viability) assays, respectively. Moreover, cysteamine and fisetin treatment ameliorated CS-mediated ROS production (p < 0.05) and diminished cell viability (p < 0.05). Lastly, CSE was found to induce cellular senescence (p < 0.001), which was significantly ameliorated by cysteamine (p < 0.001) or fisetin (p < 0.001). In conclusion, our study indicates that CS induced proteostasis/autophagy-impairment regulates mechanisms associated with AMD pathogenesis. Moreover, autophagy-inducing drugs such as cysteamine or fisetin can ameliorate AMD pathogenesis mechanisms that warrant further investigation in pre-clinical murine models.